Arabic Language as a Catalyst for Effective Learning of Islamic Studies in Western-Oriented Schools in Nigeria - Muhammad Aliyu Gambari (Journal of Arabic Language Teaching, 2025)
Arabic is crucial for a deep understanding of Islamic Studies, particularly in Western-oriented schools in Nigeria. Although its importance is acknowledged, there is a gap in empirical research on the extent to which Arabic serves as a catalyst for improving students' academic achievement. This study investigates the role of Arabic as a catalyst for effective learning of Islamic Studies and its significant relationship with academic performance. The research uses a descriptive survey method. Data were collected through questionnaires in Nigerian schools and analyzed statistically to identify correlations between variables. The findings show a significant positive relationship between knowledge of Arabic and understanding of Islamic Studies. Knowledge of Nahwu (syntax) and Sharaf (morphology) facilitates comprehension of primary texts, which enhances students' academic performance. Arabic is an essential prerequisite for effective learning of Islamic Studies. The study recommends integrating Arabic into the Islamic Studies curriculum starting from the secondary school level.